Running During Encoding Improves Word Learning for Children - Amico, Gianluca; Schaefer, Sabine (Frontiers in Psychology, 2020)
The learning of new information is an important task in everyday life, especially at a young age. Acute physical exercise can facilitate cognitive processes in multiple ways, and previous studies have shown that memory can profit from physical exercise before and during the encoding of vocabulary. The current study investigates the interplay of movement and vocabulary learning and also addresses lifespan differences in these effects. Participants were recruited in a recreational basketball club. Children (n = 24, Mage= 12.3 years; 13 girls), young adults (n = 30, Mage= 21.5 years; 17 women), and older adults (n = 24, Mage= 59.3 years; 9 women) learned twenty new pseudo-words, which corresponded to a German word. In a between-subjects design, encoding took place either while standing, while running, or while running and dribbling a basketball. Recall was assessed three times throughout the learning session and on the following day. In children, more words could be remembered in the running condition compared to the standing condition. There were no differences between conditions for the young and older adults. Age-dependent reasons for this pattern of results are further discussed and embedded into the literature of physical exercise. Our result suggests that implementing learning activities into children’s physical education or exercise activities could be beneficial.